Effect of a Connective Tissue Graft in Combination With a Single Flap Approach in the Regenerative Treatment of Intraosseous Defects. Issue 4 (1st April 2017) - Trombelli, Leonardo; Simonelli, Anna; Minenna, Luigi; Rasperini, Giulio; Farina, Roberto
Abstract : Background: In the attempt to limit the post‐surgery increase in buccal gingival recession (bREC), effect of a connective tissue graft (CTG) when combined with a buccal single flap approach (SFA) in the regenerative treatment of intraosseous defects is evaluated. Methods: Data related to 30 patients with an intraosseous defect treated with a buccal SFA with (SFA+CTG group; n = 15) or without (SFA group; n = 15) placement of a CTG and regenerative treatment were retrospectively derived at three clinical centers. bREC and probing parameters were assessed at presurgery and 6 months post‐surgery. Results: In addition to a significant attachment gain and probing depth reduction, adjunctive use of a CTG to a buccal SFA in the regenerative treatment of periodontal intraosseous defects associated with a buccal bone dehiscence resulted in a limited post‐surgery bREC, a lower prevalence of defects with a clinically detectable apical displacement of the gingival margin, and an increase in gingival width and thickness. Conclusion: Adjunctive use of a CTG in the regenerative treatment of intraosseous defects associated with buccal bone dehiscence accessed by buccal SFA may support the stability of the gingival profile.